PENENTUAN LITOLOGI LAPISAN BAWAH PERMUKAAN BERDASARKAN TOMOGRAFI SEISMIK REFRAKSI UNTUK GEOTEKNIK BENDUNGAN AIR DAERAH “X” - Hilman Sabiq; Syamsurijal Rasimeng; Karyanto Karyanto (Jurnal Geofisika Eksplorasi, 2018)
Batang Toru river which is through Kecamatan Sipirok, Kabupaten Tapanuli Selatan, will be a hydro-electric power plant, in order to require the electricity in North Sumatera area. Therefore, refraction seismic survey needed to determine the subsurface litology, as a guide in the construction of river water dam in that area. This study aims to determine lithology in the research area based on cross-section of refraction seismic tomography, and to estimate the depth and thickness of the rock layers beneath the surface of the study area. Refraction seismic tomography produces a cross section which shows the distribution of velocity value to depth, so we obtain the interpretation of rock lithology and depth estimation of each layer. The first layer is a topsoil layer with a velocity range of 100-700 m/s, the thickness of the topsoil is estimated to be about 1-10 meters. The second layer is indicated as a tuff-sandstone with medium consolidation with a velocity range of 600-1800 m/s, with an estimated thickness about 10-35 meters. The third layer is indicated as a tuff-sand rock to tuff-breccia with a value range higher than 1800 m/s, with an estimated depth of 30-40 meters from the surface.